Livelihood Vulnerability of Women in the Context of Climate Change Impacts: A Comparative Insight from Taltali Upazila of Barguna District - Mithila; Abir, Tareq Mahamud; Islam, Md. Muhimenul (CenRaPS Journal of Social Sciences, 2024)
All of humanity is affected by the negative effects of climate change, though not equally. Women are more susceptible to the effects of climate change than men are because they depend more heavily on erratic daily means of subsistence, have lower coping skills, are more likely to be poor, and face social norms and obligations that prevent them from participating in climate change processes. The purpose of this research is to ascertain how the negative effects of climate change affect women's livelihoods. The results adhered to the methodology recommendations of the descriptive study design, both in terms of qualitative and quantitative aspects. Using probability sampling, or more specifically, simple random selection techniques, a sample of 364 respondents was selected to participate in the study. Key informant interviews (KII) and focus groups discussions (FGD) were used to gather qualitative data, while household surveys were used to collect quantitative data. The outcome demonstrates how women's livelihoods in coastal areas are being disrupted by climate change. It implies that gender norms that make women vulnerable to climate change must be eliminated, and that domestic abuse must be put an end to as soon as feasible. Furthermore, there is a severe lack of progress in the development of adaptable support systems to shield coastal women from the unpredictable effects of climate change.